2008
DOI: 10.1128/aac.01641-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Surveillance Study of Telavancin Activity against Recently Collected Gram-Positive Clinical Isolates from across the United States

Abstract: Telavancin is an investigational, rapidly bactericidal lipoglycopeptide antibiotic that is being developed to treat serious infections caused by gram-positive bacteria. A baseline prospective surveillance study was conducted to assess telavancin activity, in comparison with other agents, against contemporary clinical isolates collected from 2004 to 2005 from across the United States. Nearly 4,000 isolates were collected, including staphylococci, enterococci, and streptococci (pneumococci, beta-hemolytic, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
64
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 19 publications
(24 reference statements)
10
64
1
Order By: Relevance
“…In contrast, when tested against streptococci, the impact of the revised method on the telavancin MIC results was less pronounced, which was similar to those observed for the other lipoglycopeptides (4,5). These results suggest that (i) P-80 is necessary for a more accurate MIC determination for telavancin and previous studies underestimated the drug's in vitro potency due to drug loss because of binding to plastic surfaces (1,2,(13)(14)(15) and (ii) similar to dalbavancin and oritavancin, presence of LHB provides an effect similar to that of P-80. Arhin et al (5) demonstrated that the recovery of radiolabeled [ 14 C]oritavancin from 96-well plates decreased rapidly in the absence of P-80 or LHB, while the presence of either of these reagents or of both promoted nearly 100% recovery.…”
Section: Resultscontrasting
confidence: 41%
“…In contrast, when tested against streptococci, the impact of the revised method on the telavancin MIC results was less pronounced, which was similar to those observed for the other lipoglycopeptides (4,5). These results suggest that (i) P-80 is necessary for a more accurate MIC determination for telavancin and previous studies underestimated the drug's in vitro potency due to drug loss because of binding to plastic surfaces (1,2,(13)(14)(15) and (ii) similar to dalbavancin and oritavancin, presence of LHB provides an effect similar to that of P-80. Arhin et al (5) demonstrated that the recovery of radiolabeled [ 14 C]oritavancin from 96-well plates decreased rapidly in the absence of P-80 or LHB, while the presence of either of these reagents or of both promoted nearly 100% recovery.…”
Section: Resultscontrasting
confidence: 41%
“…In contrast, telavancin, an investigational lipoglycopeptide with a dual mechanism of action, is potent, with MICs of Յ1 g/ml against all MRSA phenotypes (including hVISA and VISA) with the exception of some VRSA strains (12,13,19,23). Telavancin was recently approved in the United States and Canada for treatment of complicated skin and skin structure infections due to Gram-positive pathogens (26)(27)(28), including MRSA, and is under investigation as a oncedaily treatment for hospital-acquired pneumonia caused by Gram-positive bacteria (25).…”
mentioning
confidence: 99%
“…Telavancin exhibits more potent in vitro and in vivo activity than vancomycin against methicillin-susceptible S. aureus (MSSA), MRSA, VISA, and VRSA (10,14,23,26,30).…”
mentioning
confidence: 99%